Design of external electric field membrane less hydrogen fuel cell - Mohamed, Merghani T; Khalifa, Othman O; Hassan Abdalla Hashim, Aisha (African Academy of Advanced Studies (AAAS), 2024)
Sustainable and renewable energy sources are essential to reaching carbon neutrality on a global scale soon. In addition to their potential for producing green energy, hydrogen fuel cells have drawn a lot of interest for their ability to lower CO2 and SO2 emissions, which makes them perfect for usage in homes where people value cleanliness above all else. Hydrogen fuel cells have been around for more than a century, but their general implementation is limited by several technical issues and high costs, especially when it comes to membranes and electrodes. Traditional designs, such as PEM hydrogen fuel cells, microfluidic membrane-less fuel cells, and solid oxide fuel cells, have attempted to overcome these concerns by chemical, mechanical, and material advancements. This paper presents a novel approach that uses an external electric field to improve the efficiency and functionality of hydrogen fuel cells, resulting in the invention of the External Electric Field Membrane-less Hydrogen Fuel Cell (EEFMLHFC). The proposed idea uses the notion of oriented external electrical field electrochemical catalysis to accelerate and steer the ionic reactants—hydrogen and oxygen—towards one other, resulting in a smoother and more efficient reaction. This design eliminates the requirement for a typical membrane while also addressing common difficulties including water flooding, membrane breakdown, and material expansion caused by different heat coefficients. The EEFMLHFC achieves excellent reactant adsorption and cell power production by using porous platinum electrodes that are augmented by an external electric field and a water-cooling system. The desig